2021
DOI: 10.1088/1755-1315/755/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Meistera chinensis fruit properties: Chemical compound, antioxidant, antimicrobial, and antifungal activity

Abstract: Zingiberaceae has a large number of species in Indonesia. One of the newly discovered generations of this class is Meistera chinensis. It is widely distributed in Konawe Regency, Southeast Sulawesi. There is no information on the chemical compound and pharmacological activity of this plant. This study aims to identify chemical compounds, antibacterial, antioxidant, and antifungal of extract from Meistera chinensis fruit. Meistera chinensis fruit dry powder was extracted by maceration process using ethanol 96% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Phytochemical screening showed that M chinensis fruit extracts contained saponins, terpenoids, steroids, alkaloids, phenolics, tannins, and flavonoids. 3 The extracts exhibited antioxidant activity by scavenging DPPH radicals in a dose-dependent pattern with an IC 50 of 47.62 ± 2.93. The results of the analysis of variance on antibacterial and antifungal properties showed that there was a significant difference ( p = .00 < .05) against fungal and bacterial growth.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Phytochemical screening showed that M chinensis fruit extracts contained saponins, terpenoids, steroids, alkaloids, phenolics, tannins, and flavonoids. 3 The extracts exhibited antioxidant activity by scavenging DPPH radicals in a dose-dependent pattern with an IC 50 of 47.62 ± 2.93. The results of the analysis of variance on antibacterial and antifungal properties showed that there was a significant difference ( p = .00 < .05) against fungal and bacterial growth.…”
Section: Introductionmentioning
confidence: 94%
“…The results of the analysis of variance on antibacterial and antifungal properties showed that there was a significant difference (p = .00 < .05) against fungal and bacterial growth. 3 Meistera tomrey (Gagnep.) Škorničk & M. F. Newman is a rhizomatous geophyte and grows primarily in the wet tropical biome.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…setelah itu, dituang media ke dalam cawan petri sekitar 20 mL dan dibiarkan hingga memadat (Nurhayati et al, 2020). steroid (Karmilah et al, 2023;Musdalipah et al, 2021). Alkaloid bekerja dengan mengganggu sintesis DNA bakteri.…”
Section: Pembuatan Media Uji Antibakteriunclassified